Role of automation in waste management and recent trends. (2017) - Desai, Raghavendra; Parimala, M.
With the technology human needs are growing and the need arises for a system to manage it, maintain it and make it hassle free for the users. Let us take an example suppose you have to take attendance of 100 students daily which is a tedious and time consuming job, instead we can have a bio metric machine which can be passed among students to record attendance of students. This is an application of automation. Well, this was an example at smaller scale. When we see things in terms of enterprises which is established worldwide it becomes an important need to automate the processes that are conventional and reduce the human effort. Waste management is a critical process which involves collecting and managing waste from all the areas of the city. There are still places where people go and throw waste and litter it. We can make this process of collecting the waste as automated, where a platform can be created for people who can file complaints regarding throwing of wastes. It can also have several CC cameras installed in these types of places to monitor and help the city keep clean.